Future advancements for CSR and the sustainable development goals in a post-COVID-19 world - Perez, Andrea, 1984- (Advances in human resources management and organizational development (AHRMOD) book series., 2022)
"In light of the new reality imposed by the COVID-19 outbreaks, this book urges the scientific community to study corporate and stakeholder reactions that may lead to changes in CSR, corporate approaches to sustainability and the stakeholders' (consumers, employees, etc) psychology and behavior"--